PENTINGNYA REGULASI YANG MELINDUNGI PENGEMUDI OJEK ONLINE PEREMPUAN: The Importance of Regulations That Protect Female Online Motorcycle Drivers - Zain, Luthfiah; Retnowulandari, Wahyuni (Faculty of Law, Universitas Trisakti, 2025)
This research aims to find out the legal regulations for female online motorcycle taxi drivers, and analyze what forms of rights and legal protection are needed by female online motorcycle taxi drivers. Online motorcycle taxi is a transportation service that uses an online application. Previously, conventional motorcycle taxi transportation services were dominated by male drivers. However, as time goes by, the existence of online motorcycle taxis has made it possible for women to pursue work as online motorcycle taxi drivers. Through the participation of women in this job, we can change the view that this job is only suitable for men. Based on CEDAW (The Convention on the Elimination of All Forms of Discrimination Against Women), men and women have the same opportunities and rights to work. However, if there is discrimination against women, then this constitutes a violation of women's human rights. Therefore, with the existing rules, they should be able to be applied in the field. Women are very vulnerable and need special protection to ensure that there is work that has the potential to threaten them. The type of research used is normative, namely providing descriptive data by collecting secondary data through literature searches, and analyzing it qualitatively, as well as drawing conclusions deductively. However, based on facts on the ground, currently there is no specific law that regulates and guarantees legal protection and their rights as online motorcycle taxi drivers, especially female drivers